2006
DOI: 10.1002/anie.200600256
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Nano‐ to Microsized Spherical Assemblies of a Short Oligo(p‐phenyleneethynylene) into Superstructured Organogels

Abstract: The self-assembly of linear p-conjugated molecules to form nanoarchitectures of different morphologies is important in various fields of nanoscience and technology, particularly in the emerging field of supramolecular electronics. [1,2] In this context, oligo(p-phenyleneethynylene)s (OPEs), a class of conjugated molecules often referred as "molecular wires" has attracted much attention, particularly for the design of molecular electronic devices.[3] Although meta-and paralinked oligo-and poly(p-phenyleneethyny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(56 citation statements)
references
References 67 publications
3
53
0
Order By: Relevance
“…In addition, the variability in bands observed in the IR spectra indicated that the polymorphism in the studied systems can be diverse, as reported previously for 1 [85]. Systems, where the gel was formed by vesicles or spherical colloidal aggregates rather than the more common fibrous structures have occasionally been described in the literature [40,78,79,[86][87][88][89]. Intriguingly, bile acid-based organogelation based on colloidal aggregates in the range of hundreds of nanometers have been reported [29].…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the variability in bands observed in the IR spectra indicated that the polymorphism in the studied systems can be diverse, as reported previously for 1 [85]. Systems, where the gel was formed by vesicles or spherical colloidal aggregates rather than the more common fibrous structures have occasionally been described in the literature [40,78,79,[86][87][88][89]. Intriguingly, bile acid-based organogelation based on colloidal aggregates in the range of hundreds of nanometers have been reported [29].…”
Section: Discussionmentioning
confidence: 67%
“…For example, they have reported the formation of micrometer-size supramolecular tapes and helices through self-assembly of oligo (p-phenylenevinylene) derivatives (figure 26A) [189]. Formation of superstructures of micrometer size in a dried assembly obtained from decane was revealed by SEM imaging.…”
Section: Gels and Liquid Crystalsmentioning
confidence: 99%
“…In the gel state, the luminophores may assemble and align in a onedimensional fashion, which may result in interesting fluorescence phenomena [11][12][13][14][15]. Thus, these fluorescent organogels may find high-technological applications such as in optical devices and sensors.…”
Section: Introductionmentioning
confidence: 97%